Reproductive ecology of the great reed warbler (Acrocephalus arundinaceus) in the conditions of the drainage canal of the Poltava mining and processing plant - L. M. Litvin; A. B. Chaplygina (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. To investigate the reproduction ecology of the great warbler Acrocephalus arundinaceus in the territory of the drainage canal of the Poltava Mining and Processing Plant in order to preserve the species in the conditions of a technogenic landscape.